VD_FINDINFO Arrêt / 2021 / 920 vom 7. Oktober 2021 - VD Tribunal cantonal (2021)
DÉCISION D'IRRECEVABILITÉ, SOCIÉTÉ ANONYME, LÉGITIMATION ACTIVE ET PASSIVE | 56 al. 1 LPGA, 50 LPA-VD, 82 LPA-VD, 94 al. 1 let. d LPA-VD